Examination of musculoskeletal injuries - Shultz, Sandra J., 1961- (Athletic training education series., 2010)
"The third edition of Examination of Musculoskeletal Injuries assists both current and future rehabilitation professionals in recognizing musculoskeletal injuries, performing musculoskeletal examinations of athletic injuries, and evaluating if and when to refer clients to a physician's care. The text will help students master the skills required for completing the certified athletic trainer examination by thoroughly covering all the content in this area of specialization set forth in the National Athletic Trainers' Association (NATA) Athletic Training Educational Competencies." "Completely updated, the third edition further elaborates on clinical decision making, problem solving, and integration of skill application. Improved chapter-opening scenarios present open-ended real-life situations that initiate discussion of the complexity of athletic injury examination. Data tables that report the sensitivity and specificity of special tests strengthen the evidence-based selection of those tests as they are used in the examination procedure. Also, revised information in the functional anatomy and injury recognition sections form a more cohesive connection with the musculoskeletal examination process." "Examination of Musculoskeletal Injuries, Third Edition, features an online student resource (OSR) that will help students better understand the material. The OSR includes printable examination checklists; tables detailing range of motion, neurological conditions, and strength; and superb full-color photographs of skin ailments that will enhance students' ability to identify skin disorders."--BOOK JACKET.